Urinary protein-to-creatinine ratio in guinea pigs (Cavia porcellus): Reference range and the effect of age and sex - Kovarikova, Simona; Blahova, Jana; Truhlarova, Alena; Baslerova, Sona; Krepinska, Iva; Jekl, Vladimir (The Veterinary record, 2024)
BACKGROUND: There are currently few reports on the normal urinary protein-to-creatinine (UPC) ratio of guinea pigs, and there is little information on the effects of age and sex on this parameter. METHODS: Urinary protein and creatinine concentrations were measured in a total of 161 clinically healthy guinea pigs, and the UPC ratio was subsequently calculated. The effect of age and sex on these parameters was assessed using Mann-Whitney U tests. Using these data, UPC ratio reference ranges were established. RESULTS: Guinea pig pups younger than 6 months had a significantly higher UPC ratio than adult animals (median UPCs of 1.48 and 0.56, respectively). There was no effect of sex on this parameter. The reference range for the UPC ratio in adult guinea pigs was set at 0.12-2.21. For guinea pigs younger than 6 months, the reference range for the UPC ratio was set at 0.4-3.1. LIMITATIONS: This study was limited by the lack of blood analysis, which could reveal a subclinical health problem that could affect renal function and the extent of proteinuria. CONCLUSION: In guinea pigs, the UPC ratio is influenced by age but not by sex. Therefore, the reference range established for adult guinea pigs cannot be used for pups younger than 6 months.